Paternal involvement and peer competence in young children: the mediating role of playfulness - Chunyan Liang; Xinwen Bi (Frontiers in Psychology)
ObjectiveThe capacity to interact with peers during early childhood can profoundly and enduringly influence later development and adaptation. Previous research has indicated that paternal involvement plays a vital role in shaping children’s peer competence. However, limited research has been conducted on this association within the Chinese cultural contexts or on the potential mechanisms that underlie it. Therefore, the present study aims to investigate whether there is a close link between paternal involvement and peer competence in Chinese young children, as well as whether children’s playfulness mediates this relationship.MethodThe Chinese version of the Paternal Involvement Questionnaire (FIQ) was distributed to 359 fathers with children (4–6 years old). Children’s Playfulness Scale (CPS) and Ability to Associate With Partners Scale (AAPS) were distributed to the children’s mothers.Results(1) There are positive correlations between paternal involvement, young children’s playfulness and peer competence after controlling for the demographic variables of age and gender. (2) Paternal involvement is positively related to young children’s peer competence. (3) Playfulness partially mediated the relationship between paternal involvement and children’s peer competence. Findings from this study emphasize the significance of paternal involvement in enhancing young children’s peer competence, while also highlighting the value of positive emotional traits such as playfulness for fostering family interaction and promoting young child development.